2019
DOI: 10.1038/s41598-019-39499-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic protein changes in the perihaemorrhagic zone of Surgically Treated Intracerebral Haemorrhage Patients

Abstract: The secondary injury cascades exacerbating the initial brain injury following intracerebral haemorrhage (ICH) are incompletely understood. We used dual microdialysis (MD) catheters placed in the perihaemorrhagic zone (PHZ) and in seemingly normal cortex (SNX) at time of surgical ICH evacuation in ten patients (range 26–70 years). Routine interstitial MD markers (including glucose and the lactate/pyruvate ratio) were analysed and remaining microdialysate was analysed by two-dimensional gel electrophoresis (2-DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…In a recent study of ICH patients, using a similar study design we found a difference in proteins expressed in the perihemorrhagic zone (PHZ) compared to seemingly normal cortex (SNX) [13]. In light of the results of this present study it is likely that several proteins evaded detection by adsorbing to the CMD membranes.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In a recent study of ICH patients, using a similar study design we found a difference in proteins expressed in the perihemorrhagic zone (PHZ) compared to seemingly normal cortex (SNX) [13]. In light of the results of this present study it is likely that several proteins evaded detection by adsorbing to the CMD membranes.…”
Section: Discussionsupporting
confidence: 61%
“…The proteomic analysis of the microdialysate of the three patients has been previously published [13] along with a detailed description of the sample preparation. Briefly, 40 μL of each sample was applied onto an Albumin & IgG Depletion column (GE Healthcare, Uppsala, Sweden), before being desalted and lyophilized.…”
Section: Sample Preparation Preparation Of Dialysate Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microdialysate was collected at a time corresponding to 72 hours after ICH onset. The results of 2-DE of this microdialysate has been previously published (13).…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…The proteomic analysis of the microdialysate of the three patients has been previously published (13) along with a detailed description of the sample preparation. Briefly, 40 µL of each sample was applied onto an Albumin & IgG Depletion column (GE Healthcare, Uppsala, Sweden), before being desalted and lyophilized.…”
Section: Sample Preparation Preparation Of Dialysate Samplesmentioning
confidence: 99%